Reliability and validity of the sensorimotor control tests in patients with neck pain and its associated disorders : a systematic review and meta-analysis. - Lavapuro, Joona (My University, 2023)
Purpose: The objectives of this systematic review were to synthesize the current evidence regarding neck sensorimotor testing in patients with neck pain, the ability to make a difference between different neck pain patient groups and healthy controls by testing, and to recognize factors that might affect test results. Methods: We performed the data search using PubMed, Embase, PsycINFO, CINAHL, and Scopus databases based on three groups of keywords: neck pain, sensorimotor tests, and reliability and validity of the clinical tests. We used a two-step screening process to identify studies. Furthermore, we screened the reference lists for additional studies. We included all neck sensorimotor tests in the review but analyzed only those for which at least three studies reported the same variable and parameter results. Hedges g was used to present the difference between different neck pain groups and between different neck pain groups and those without symptoms. We assessed the quality of the studies using the QUADAS tool. Results: The final review included 29 studies, of which 20 were related to the joint position error (JPE) test, four to the smooth pursuit neck torsion (SPNT) test and five to the balance test. The studied neck pain groups were traumatic (WAD), non-specific neck pain (NSNP), and neck pain with dizziness. According to our meta-analysis, sensorimotor control was poorer in all tests in patients with neck pain compared to healthy controls (effect size 0.17-3.54). Furthermore, the JPE in the WAD group was higher than the NSNP group (effect size 0.24). The size of the difference between the groups seemed to be influenced by the intensity of the pain and the presence of dizziness. Conclusion: To evaluate sensorimotor control as a phenomenon, we should be able to determine which variables can affect the test results. According to our review, pain intensity and dizziness appear to affect the results of sensorimotor tests. However, there still needs to be more information on the effects of various factors on sensorimotor control. Therefore, the reference standard is still missing.